1977
DOI: 10.1073/pnas.74.5.2089
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nonspecific immunity to Klebsiella pneumoniae infection by a synthetic immunoadjuvant (N-acetylmuramyl-L-alanyl-D-isoglutamine) and several analogs.

Abstract: N-Acetylmuramyl-L-alanyl-D-isoglutamine and four other synthetic adjuvants that are structural analogs of part of the mycobacterial peptidoglycan monomer are shown to enhance the nonspecific immunity of mice infected by Kiebsiella pneumoniae. These compounds are active by various routes, including oral administration; they are also effective when administered after challenge. Of the seventeen other analogs tested, none is able to increase significantly resistance to infection, although seven of these molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(81 citation statements)
references
References 21 publications
(11 reference statements)
5
73
0
Order By: Relevance
“…These results were similar to those obtained with other immunostimulatory adjuvants, many of which are TLR agonists (13). Those TLR agonists that have been used as adjuvants include lipopolysaccharide (23), CpG DNA (24,25), muramyl dipeptides (26,27), monophosphoryl lipid A (28), and imiquimod (29,30).…”
Section: Discussionsupporting
confidence: 73%
“…These results were similar to those obtained with other immunostimulatory adjuvants, many of which are TLR agonists (13). Those TLR agonists that have been used as adjuvants include lipopolysaccharide (23), CpG DNA (24,25), muramyl dipeptides (26,27), monophosphoryl lipid A (28), and imiquimod (29,30).…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, Chedid et al and the others reported that several MDP analogs enhanced host resistance to bacterial infection (11, 13,14,[40][41][42]. The aim of the present report is twofold: to give the results of a detailed study of the augmentation of host resistance to bacterial infection induced by MDP(Ala), and to evaluate the efficacy of MDP analogs in which the L-alanyl residue of MDP(Ala) was replaced with another L-amino acid.…”
mentioning
confidence: 99%
“…In preliminary experiments, daily administration of 0.3 mg/kg LSN B for five days resulted in a sixfold increase in peripheral neutrophils, but no ( FK-156) and isohematinic acid, which enhance the function of neutrophils and thereby augment host resistance to bacterial infection (4,8,13,18). When the activities of some of these compounds are compared with that of LSN B, in our assay system (18), the effects of LSN B were stronger than those of MDP and isohematinic acid, and comparable with those of human recombinant G-CSF (data not shown).…”
Section: Discussionmentioning
confidence: 99%